The xylanase inhibitor TAXI‐III counteracts the necrotic activity of a Fusarium graminearum xylanase in vitro and in durum wheat transgenic plants. (15th December 2014) - Moscetti, Ilaria; Faoro, Franco; Moro, Stefano; Sabbadin, Davide; Sella, Luca; Favaron, Francesco; D'Ovidio, Renato
Summary The xylanase inhibitor TAXI‐III has been proven to delay Fusarium head blight (FHB) symptoms caused by Fusarium graminearum in transgenic durum wheat plants. To elucidate the molecular mechanism underlying the capacity of the TAXI‐III transgenic plants to limit FHB symptoms, we treated wheat tissues with the xylanase FGSG_03624, hitherto shown to induce cell death and hydrogen peroxide accumulation. Experiments performed on lemmas of flowering wheat spikes and wheat cell suspension cultures demonstrated that pre‐incubation of xylanase FGSG_03624 with TAXI‐III significantly decreased cell death. Most interestingly, a reduced cell death relative to control non‐transgenic plants was also obtained by treating, with the same xylanase, lemmas of TAXI‐III transgenic plants. Molecular modelling studies predicted an interaction between the TAXI‐III residue H395 and residues E122 and E214 belonging to the active site of xylanase FGSG_03624. These results provide, for the first time, clear indications in vitro and in planta that a xylanase inhibitor can prevent the necrotic activity of a xylanase, and suggest that the reduced FHB symptoms on transgenic TAXI‐III plants may be a result not only of the direct inhibition of xylanase activity secreted by the pathogen, but also of the capacity of TAXI‐III to avoid host cell death.